2017
DOI: 10.1038/emm.2017.207
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte toll-like receptor 4 mediates lipopolysaccharide-induced hepcidin expression

Abstract: Hepcidin expression is induced by inflammatory molecules such as lipopolysaccharide (LPS) via a macrophage-mediated pathway. Although hepatocytes directly respond to LPS, the molecular mechanism underlying toll-like receptor (TLR)-dependent hepcidin expression by hepatocytes is mostly unknown. Here we show that LPS can directly induce the mRNA expression and secretion of hepcidin by hepatocytes via TLR4 activation. Using hepatocytes deficient in TLR4, myeloid differentiation factor 88 (MyD88) and TIR domain-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 36 publications
0
40
0
Order By: Relevance
“…Kupffer cells activated by LPS produce pro-inflammatory cytokines IL-18, IL-1b, and IL-12, leading to induction of NK cells and cytotoxic T cells (Takahashi et al, 1996;Seki et al, 2001). TLR4 expressed by hepatocytes responds to LPS and regulates the expression of hepcidin, a key iron-regulatory protein implicated in obesity and NAFLD, via the MyD88-IRAK-TRAF6-JNK-AP-1 axis (Lu et al, 2016;Lee et al, 2017). TLR4 expressed by hepatocytes responds to LPS and regulates the expression of hepcidin, a key iron-regulatory protein implicated in obesity and NAFLD, via the MyD88-IRAK-TRAF6-JNK-AP-1 axis (Lu et al, 2016;Lee et al, 2017).…”
Section: Microbiome-induced Induction Of Liver Inflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…Kupffer cells activated by LPS produce pro-inflammatory cytokines IL-18, IL-1b, and IL-12, leading to induction of NK cells and cytotoxic T cells (Takahashi et al, 1996;Seki et al, 2001). TLR4 expressed by hepatocytes responds to LPS and regulates the expression of hepcidin, a key iron-regulatory protein implicated in obesity and NAFLD, via the MyD88-IRAK-TRAF6-JNK-AP-1 axis (Lu et al, 2016;Lee et al, 2017). TLR4 expressed by hepatocytes responds to LPS and regulates the expression of hepcidin, a key iron-regulatory protein implicated in obesity and NAFLD, via the MyD88-IRAK-TRAF6-JNK-AP-1 axis (Lu et al, 2016;Lee et al, 2017).…”
Section: Microbiome-induced Induction Of Liver Inflammationmentioning
confidence: 99%
“…In fructose-induced NAFLD in mice, the activation of Kupffer cells through TLR4-dependent mechanism is mediated via a MyD88dependent signaling pathway, leading to induction of hepatic TNF-a mRNA, formation of reactive oxygen species (ROS), and insulin resistance (Rivera et al, 2007;Spruss et al, 2009). TLR4 expressed by hepatocytes responds to LPS and regulates the expression of hepcidin, a key iron-regulatory protein implicated in obesity and NAFLD, via the MyD88-IRAK-TRAF6-JNK-AP-1 axis (Lu et al, 2016;Lee et al, 2017). In liver sinusoidal endothelial cells (LSEC), TLR4 activation leads to induced production of TNF-a and ROS, but in vivo they are mostly exhibiting tolerance to LPS and its effect is probably minimal (Sarphie et al, 1996;Uhrig et al, 2005).…”
Section: Microbiome-induced Induction Of Liver Inflammationmentioning
confidence: 99%
“…TLRs/MyD88 signaling has been shown to also contribute to the regulation of hepcidin, a molecule involved in cellular and systemic iron metabolism ( Wang et al, 2009 ; Xiong et al, 2016 ; Lee et al, 2017 ). Hepcidin, encoded by the HAMP gene, is the major regulator of intestinal iron absorption and iron recycling from macrophages ( Hentze et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…In that report, it was demonstrated that the selective blockade of TLR2 or TLR4 inhibited the overexpression of TF following activation with H4, among other histones (13). Notably, the expression of TLR4 has been reported in hepatocytes and it may be implicated in the overexpression of hemostatic factors and/or HNF4α as well as TF (39). Additional studies using animal models may aid to define if these changes in the coagulant state may occur in vivo and if overexpression of hemostatic factors is also detectable in plasma following a challenge with DNA or H4.…”
Section: Discussionmentioning
confidence: 94%